2021
DOI: 10.1016/j.scitotenv.2021.145727
|View full text |Cite
|
Sign up to set email alerts
|

Development of a large volume concentration method for recovery of coronavirus from wastewater

Abstract: Levels of severe acute respiratory coronavirus type 2 (SARS CoV 2) RNA in wastewater could act as an effective means to monitor coronavirus disease 2019 (COVID-19) within communities. However, current methods used to detect SARS CoV 2 RNA in wastewater are limited in their ability to process sufficient volumes of source material, inhibiting our ability to assess viral load. Typically, viruses are concentrated from large liquid volumes using two stage concentration, primary and secondary. Here, we evaluated a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…The Cp Select method yielded an average of 29.29% BCoV recovery, which is similar to results reported in other studies using MS2 and OC43 for recovery ( (Forés et al, 2021;McMinn et al, 2021). When comparing the BCoV recovery between the two methods under consideration, the Cp Select method outperformed EMF in terms of both median value and average recovery value, as shown in Figure 1.…”
Section: Time Comparison Of Emf and Cp Select Concentration Methodssupporting
confidence: 85%
“…The Cp Select method yielded an average of 29.29% BCoV recovery, which is similar to results reported in other studies using MS2 and OC43 for recovery ( (Forés et al, 2021;McMinn et al, 2021). When comparing the BCoV recovery between the two methods under consideration, the Cp Select method outperformed EMF in terms of both median value and average recovery value, as shown in Figure 1.…”
Section: Time Comparison Of Emf and Cp Select Concentration Methodssupporting
confidence: 85%
“…Additionally, the filter used in our study has a larger membrane area (1.8 m 2 for inuvai R180 vs 1.5 m 2 for Rexeed S15) and larger fiber inner diameters (220 μm for inuvai R180 vs 185 μm for Rexeed S15). In addition to the optimized elution and secondary concentration protocols, such features might help justify the differences registered in the recovery efficiencies of our study and McMinn et al (2021).…”
mentioning
confidence: 86%
“…Gonzalez et al (2020), testing the CDC assay (N1, N2, and N3), reported different theoretical limits of detection depending on the RT-qPCR assay used but the LoD were similar to those obtained in our study. A comparison between the performance of our method (evaluated through LoD and LoQ) and the method reported by McMinn et al (2021) would have been useful, given that the authors have also used hollow-fiber filters for primary concentration, but such parameter information is missing on the former report. In fact, information on LoQ is missing from most publications with very few exceptions, such as LaTurner et al…”
Section: Rt-qpcr Efficiencymentioning
confidence: 99%
See 2 more Smart Citations